Quality Indicators for Depression Treatment in Primary Care: A Systematic Literature Review - Duhoux, Arnaud; Fournier, Louise; Menear, Matthew (Current Psychiatry Reviews, 2011)
Introduction: Depression is a mental disorder that is common and chronic, especially if it is initially undertreated. It is now widely recognized that primary care providers have an important role to play in the detection and treatment of depression. However, ensuring quality depression care remains a challenge. Quality indicators for the treatment of depression can help monitor the treatment received by people suffering from depression in primary care and guide improvements needed in that sector. Objectives: To systematically review indicators used to measure the quality of depression treatment in primary care and explore factors leading to divergent results. Method: The literature on the quality of depression treatment was reviewed using “360search”, a federated search engine for searching across multiple databases from a single interface. Databases searched included Pubmed, Embase and PsycINFO and keywords were depression, depressive disorder, quality, treatment, indicator, adequacy, adherence, concordance, clinical guideline and guideline. Additional articles were also identified through a manual search of the reference section of retrieved articles. Results: Though mostly based on recommendations from clinical practice guidelines, a great variety of indicators were observed. Most studies used rudimentary indicators to measure the quality of depression treatment, especially for psychotherapy. Studies also differed greatly with respect to the methods used, thus limiting the comparability of results. However, whatever the chosen method, most studies reveal that a large proportion of people with depression do not receive minimally adequate treatment in primary care settings. Conclusion: The implications of these findings and future research directions are discussed.
Keywords: drug dosage